Perempuan dengan Disabilitas Merespon Covid-19 : Sebuah Perspektif Pekerjaan Sosial Feminis - Ro'fah, Ro'fah (INKLUSI, 2022)
This research shows that --reinforcing existing research-- women with disabilities experience quite complex obstacles and impacts of Covid 19. The intersection between disability and gender creates the seriousness and complexity of the impacts experienced. The economic and social impact faced by women with disabilities is strengthened by their already vulnerable position economically and socially: lack of accessibility, social protection policies that are not inclusive and cultural factors still stigmatizing. However, in contrast to the assumptions about powerlessness and dependency, these women are strong figures whose resilience has been built. The Bantul earthquake that made them disabled has shaped them as resilient women who see the impact of Covid as a lighter disaster. These women even see Covid as a medium to form a positive identity and challenge stigma, prejudice, and social construction about the inability of women with disabilities to become mothers and wives. Penelitian ini menunjukkan bahwa --menguatkan penelitian yang sudah ada-- perempuan dengan disabilitas mengalami hambatan dan dampak Covid 19 yang cukup kompleks. Persinggungan antara disabilitas dan gender melahirkan keseriusan dan kompleksitas dampak yang dialami. Dampak ekonomi dan sosial yang dihadapi perempuan penyandang disabilitas dikuatkan dengan posisi mereka yang sudah rentan secara ekonomi dan sosial:  minimnya aksesibilitas, kebijakan perlindungan sosial yang tidak inklusif dan juga faktor kultural yang masih menstigmasi. Namun, berbeda dengan asumsi tentang ketidakberdayaan dan ketergantungan, perempuan perempuan ini adalah sosok kuat yang sudah terbangun resiliensinya. Gempa Bantul yang menjadikan mereka penyandang disabilitas telah membentuk mereka sebagai perempuan reselien yang melihat dampak Covid sebagai musibah yang lebih ringan. Perempuan perempuan ini bahkan melihat Covid sebagai media mereka membentuk identitas positif dan menggugat stigma dan prejudice dan konstruksi sosial  tentang ketidakmampuan perempuan disabilitas menjadi ibu dan istri.